1993
DOI: 10.1001/jama.1993.03500030059033
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hepatitis C Virus Seropositivity in Heterosexual Couples

Abstract: These results provide little evidence of HCV sexual transmission but are consistent with infrequent sexual transmission. They corroborate the importance of injection drug use and transfusion of blood or blood products in transmitting HCV and underscore the importance of ascertaining parenteral exposures when examining sexual transmission of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…In those studies limited to individuals without a history of injection drug use, factors predictive of anti-HCV positivity included the number of recent and lifetime partners, high risk sexual practices (variably defined), other STDs, and anti-HIV positivity. [7][8][9][10][11][12] These factors are consistent with a sexual route of transmission.…”
Section: What Is the Prevalence Of Hcv In Persons At Risk For Stds?supporting
confidence: 65%
“…In those studies limited to individuals without a history of injection drug use, factors predictive of anti-HCV positivity included the number of recent and lifetime partners, high risk sexual practices (variably defined), other STDs, and anti-HIV positivity. [7][8][9][10][11][12] These factors are consistent with a sexual route of transmission.…”
Section: What Is the Prevalence Of Hcv In Persons At Risk For Stds?supporting
confidence: 65%
“…Multiple studies have reported that HCV is inefficiently transmitted sexually. [14][15][16][17] We cannot exclude the possibility that a more established risk factor (e.g., syringe sharing) or frequency of injection may be indirectly responsible for this association.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the possibility that some of the individuals in the drug users group who selfreported as non-IDUs may have injected drugs in the past. However, the risk of sexual transmission of an HCV infection is associated with a history of multiple sexual partners and a lack of condom usage (Alter, 1990;Osmond, 1993;Rauch, 2005). Thus, the high prevalence of HCV infection in both risk groups in this study could be explained by the large number of subjects who said that they never use condoms.…”
Section: Resultsmentioning
confidence: 74%